Exploring female otolaryngologists’ experiences with gender bias and microaggressions: a cross sectional Canadian survey - Amanda C. Hu; Kelly Nguyen; Tanya K. Meyer (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Gender bias is behavior that shows favoritism towards one gender over another. Microaggressions are defined as subtle, often unconscious, discriminatory, or insulting actions that communicate demeaning or negative attitudes. Our objective was to explore how female otolaryngologists experience gender bias and microaggressions in the workplace. Methods Anonymous web-based cross-sectional Canadian survey was distributed to all female otolaryngologists (attendings and trainees) using the Dillman’s Tailored Design Method from July to August of 2021. Quantitative survey included demographic data, validated 44-item Sexist Microaggressions Experiences and Stress Scale (MESS) and validated 10-item General Self-efficacy scale (GSES). Statistical analysis included descriptive and bivariate analysis. Results Sixty out of 200 participants (30% response rate) completed the survey (mean age 37 ± 8.3 years, 55.0% white, 41.7% trainee, 50% fellowship-trained, 50% with children, mean 9.2 ± 7.4 years of practice). Participants scored mild to moderate on the Sexist MESS—Frequency (mean ± standard deviation) 55.8 ± 24.2 (42.3% ± 18.3%), Severity 46.0 ± 23.9 (34.8% ± 18.1%), Total 104.5 ± 43.7 (39.6% ± 16.6%) and high on GSES (32.7 ± 5.7). Sexist MESS score was not associated with age, ethnicity, fellowship-training, having children, years of practice, or GSES. In the sexual objectification domain, trainees had higher frequency (p = 0.04), severity (p = 0.02) and total MESS (p = 0.02) scores than attendings. Conclusions This was the first multicenter, Canada-wide study exploring how female otolaryngologists experience gender bias and microaggressions in the workplace. Female otolaryngologists experience mild to moderate gender bias, but have high self-efficacy to manage this issue. Trainees had more severe and frequent microaggressions than attendings in the sexual objectification domain. Future efforts should help develop strategies for all otolaryngologists to manage these experiences, and thereby improve the culture of inclusiveness and diversity in our specialty. Graphical Abstract